Comparative Effectiveness of Coconut Shell Charcoal and Rice Husk Ash as Adsorbents in Filtration Systems for Iron (Fe) and Manganese (Mn) Removal from Groundwater - Hidayat Hidayat; Haderiah Haderiah; Muh. Ikbal Arif (Direktorat Politeknik Kesehatan Makassar, 2026)
Clean water is a vital basic need for human life. However, in several areas such as Makassar City, drilled well water is often contaminated by heavy metals such as iron (Fe) and manganese (Mn) that exceed the quality standard thresholds established in Peraturan Menteri Kesehatan No. 2 Tahun 2023 concerning drinking water quality standards. This study aimed to determine the effectiveness of coconut shell charcoal and rice husk ash as filtration media in reducing Fe and Mn levels in drilled well water. The study employed a quasi-experimental design using a simple column filtration system with measurements conducted before and after treatment. Water samples were collected from drilled wells in Paccerakkang Village, Biringkanaya District, Makassar City, and experiments were conducted using three treatments: control, coconut shell charcoal filtration, and rice husk ash filtration with repeated observations over three days. The results showed that both coconut shell charcoal and rice husk ash were effective as natural filtration media. Coconut shell charcoal reduced Fe levels by an average of 96.26% and Mn levels by 100%, while rice husk ash reduced Fe levels by an average of 97.45% and Mn levels by 100%. These results indicate that rice husk ash demonstrated slightly higher effectiveness in reducing Fe concentrations compared to coconut shell charcoal. It can be concluded that coconut shell charcoal and rice husk ash can serve as alternative natural filtration media for community-based clean water treatment. These materials are low-cost, locally available, and capable of significantly improving well water quality. Further research is recommended to explore combinations of filtration media, variations in media thickness, and different contact times to optimize filtration performance